TSG-6 inhibits osteoclast activity via an autocrine mechanism and is functionally synergistic with osteoprotegerin. - Mahoney, D; Swales, C; Athanasou, N; Bombardieri, M; Pitzalis, C; Kliskey, K; Sharif, M; Day, A; Milner, C; Sabokbar, A (2011)
OBJECTIVE: TSG-6 (the product of tumor necrosis factor [TNF]-stimulated gene 6) has a potent inhibitory effect on RANKL-mediated bone erosion. The aim of this study was to compare the activity of TSG-6 with that of osteoprotegerin (OPG) and to investigate its role as an autocrine modulator of cytokine-mediated osteoclast formation/activation. We also determined TSG-6 expression in inflammatory joint disease. METHODS: The effects of TSG-6, OPG, and the inflammation mediators TNFα, interleukin-1 (IL-1), and IL-6 on the formation of osteoclasts from peripheral blood mononuclear cells and synovial fluid (SF) macrophages were determined by tartrate-resistant acid phosphatase staining. Lacunar resorption and filamentous actin ring formation were measured as indicators of osteoclast activity. The amount of TSG-6 in culture media or SF was quantified by enzyme-linked immunosorbent assay, and expression of TSG-6 in synovial tissue was assessed by immunohistochemistry. RESULTS: TSG-6 acted in synergy with OPG to inhibit RANKL-mediated bone resorption and was produced by osteoclast precursors and mature osteoclasts in response to TNFα, IL-1, and IL-6. Expression of TSG-6 correlated with inhibition of lacunar resorption; this effect was ameliorated by an anti-TSG-6 antibody. The level of TSG-6 protein was determined in SF from patients with various arthritides; it was highest in patients with inflammatory conditions such as rheumatoid arthritis, in which it correlated with the amount of TSG-6 immunostaining in the synovium. TSG-6 inhibited the activation but not the formation of osteoclasts from SF macrophages. CONCLUSION: In the presence of inflammatory cytokines, osteoclasts produced TSG-6 at concentrations that are sufficient to inhibit lacunar resorption. This may represent an autocrine mechanism to limit the degree of bone erosion during joint inflammation.